Citizenship pedagogies in Asia and the Pacific - Kennedy, Kerry J.; Lee, W. O. 1954-.; Grossman, David L.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
How are students in Asia and the Pacific taught to be effective citizens? Following two successful volumes previously published in this series, Citizenship Education in Asia and the Pacific: Concepts and Issues and Citizenship Curriculum in Asia and the Pacific, this volume focuses on citizenship pedagogies that are promoted by governments in the region, advocated by scholars, and adapted in the schools and classrooms where citizenship education takes place every day. Thirteen case studies from diverse societies in Asia and the Pacific highlight the ways in which teachers and students think about, experience or plan for citizenship teaching and learning. Different methods vignettes, student surveys, case studies and literature reviews are used to portray these experiences, from both macro- and micro-analytic perspectives. The wide array of case studies provides rich information and insights into the realities and possibilities of pedagogies for citizenship across the region.
List of Abbreviations.- List of Tables.-List of Figures.- Foreword: Ian DAVIES.- Introduction: Pedagogies: Possibilities and Realities for Citizenship Education.- Kerry J. KENNEDY.- Part I: Conceptual Overview.- 1. Talking about Pedagogy: Classroom Discourse and Citizenship Education: David L. GROSSMAN.- Part II: North and East Asia.- 2. Pedagogies of Cultural Integration in Chinese Citizenship Education: ZHAO Zhenzhou and Gregory P. FAIRBROTHER.- 3.The Effectiveness of Action Learning in the Teaching of Citizenship Education: A Hong Kong Case Study: Teresa CHAI YIP Wai Lin, David GALLOWAY and Wing On LEE.- 4. Structure and Agency: A Comparison of Youth Learning of Citizenship in Taipei and Calgary: Jennifer Wen Shya LEE.- 5. Exemplary Social Studies Lessons in Japan: Pedagogy for Effective Citizenship Education: Tomoyuki KOBARA.- PART III: South and Southeast Asia.- 6. Citizenship Education in Pakistan: Caught in the Stranglehold of Transmission Pedagogies: Bernadette L. DEAN.- 7. Indonesian Students and their Citizenship-Related Attributes: Implications for Instructional Strategies and Pedagogical Practices in Civic Education: Gregory Arief D. LIEM and Dennis M. MCINERNEY.- 8. Pedagogical Approaches to Citizenship Education in the Varied Contexts of Secondary Schools in the Philippines: Sherlyne A. ALMONTE-ACOSTA.- 9. Pedagogies for Citizenship Education in Thailand: The Gap between Government Policy and Implementation: Nuttaporn LAWTHONG.- 10. Simple Ideological Dupes of National Governments Teacher Agency and Citizenship Education in Singapore: Jasmine Boon-Yee SIM.- Part IV: Pacific Islands and the Pacific Rim.- 11. Civics Education in Fiji: Contradiction or Pedagogy of Hope Cresantia F. KOYA.- 12. Civics and Citizenship Education in Australia: Developing Au-thentic and Engaging Pedagogies to Empower Young Citizens:Libby TUDBALL.- 13. Embedding Education for Citizenship in Pedagogical Practices: The Case of New Zealand: Carol MUTCH.- 14. Issues-Centred Pedagogy and Classroom Climate for Discussion: A View from the United States: Carole L. HAHN.- Part V: Conclusion and Review.- 15. Multiple Modalities of Asia-Pacific Citizenship Pedagogies: Eclectic Concepts, Hybridised Approaches and Teachers? Preferences: Wing On Lee.- Notes on the Authors.- References. Index.
Electronic reproduction.
Keywords: Citizenship -- Study and teaching -- Asia; Citizenship -- Study and teaching -- Pacific Area; Civics -- Study and teaching -- Asia; Civics -- Study and teaching -- Pacific Area; Comparative education; Teaching -- Pacific Area; Education -- Pacific Area; Electronic books